Borders (The Netherlands) - Abbenhuis, Maartje (1914-1918-online. International Encyclopedia of the First World War, 2014)
The borders of the Netherlands were an important site of war experience for the Dutch, as well as a contested site of war interaction for the belligerents.
Keywords: Elektrozaun; Neutralität; Weltkrieg (1914–1918)